Akad Mudharabah Berbasis Maqasid Syariah dalam Mendukung Islamic Corporate Governance (ICG) - Muhamad Labiq Setiawan; Naela Khodikotul Amanah; Metiya Fatikhatur Riziqiyah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
The mudharabah contract is a primary instrument in Islamic finance, normatively oriented toward partnership and profit sharing. However, the practice of mudharabah in Islamic financial institutions shows a tendency toward the dominance of formal compliance approaches and excessive prudence, potentially shifting the substance of the contract from the principle of partnership to a financing pattern that resembles a debt-based contract. This study aims to reconstruct the mudharabah contract based on maqasid sharia in order to support the strengthening of Islamic Corporate Governance (ICG). The research method used is descriptive qualitative through a literature study of classical and contemporary maqasid sharia literature, Islamic accounting standards, DSN-MUI fatwas, and reputable scientific journals. The results of the study indicate that the integration of maqasid sharia as a basic value with the principles of Islamic Corporate Governance as a control system can strengthen the implementation of the mudharabah contract substantively. This study emphasizes that the mudharabah contract needs to be understood not merely as a formal fiqh contract, but as a value-based governance instrument oriented towards justice, welfare, and sustainability of Islamic financial institutions.